2004
DOI: 10.5194/angeo-22-2473-2004
|View full text |Cite
|
Sign up to set email alerts
|

Shell-like configuration in O<sup>+</Sup> ion velocity distribution at high altitudes in the dayside magnetosphere observed by Cluster/CIS

Abstract: Abstract. We report shell-like configurations seen in O + ion velocity distributions. One case was observed above 8 R E in radial distance in the dayside magnetosphere, presumably in the mantle region, during the observation period of 09:30-10:00 UT on 12 April 2001 by the CIS instrument on board the Cluster satellite. This shell-like configuration was different from so-called "conics" or "beams": the lower energy (cold) population and the higher energy partial shell part were seen together, but there was no o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Primary outputs of the model are density n , temperature T , and parallel velocity v ∥ of the outflowing H + , He + and O + ions. The model considers the contributions from all ion distributions, including nonthermal or nonisotropic distributions such as ion conics, transversely accelerated ions, ion beams, upwelling ions, upflowing ions, or shell‐like distributions [ Klumpar , 1979; Hultqvist , 1983; Yau et al , 1984, 1985; Moore et al , 1986; Thelin et al , 1990; Kondo et al , 1990; Peterson et al , 1992; Miyake et al , 1993; André et al , 1994; Joko et al , 2004]. However, previous observations have revealed that such nonthermal or nonisotropic distributions do not always occur [e.g., Yau et al , 1984; Thelin et al , 1990; Kondo et al , 1990].…”
Section: Statistical Model Of Outflowing Suprathermal Ionsmentioning
confidence: 99%
“…Primary outputs of the model are density n , temperature T , and parallel velocity v ∥ of the outflowing H + , He + and O + ions. The model considers the contributions from all ion distributions, including nonthermal or nonisotropic distributions such as ion conics, transversely accelerated ions, ion beams, upwelling ions, upflowing ions, or shell‐like distributions [ Klumpar , 1979; Hultqvist , 1983; Yau et al , 1984, 1985; Moore et al , 1986; Thelin et al , 1990; Kondo et al , 1990; Peterson et al , 1992; Miyake et al , 1993; André et al , 1994; Joko et al , 2004]. However, previous observations have revealed that such nonthermal or nonisotropic distributions do not always occur [e.g., Yau et al , 1984; Thelin et al , 1990; Kondo et al , 1990].…”
Section: Statistical Model Of Outflowing Suprathermal Ionsmentioning
confidence: 99%